2007
DOI: 10.1179/016164107x159243
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and transcriptional assessment of a mild SMA model

Abstract: Spinal muscular atrophy (SMA) is caused by survival of motor neuron (SMN) deficiency, leading to specific motor neuron attrition. The time course and molecular pathophysiologic etiology of motor neuron loss observed in SMA remains obscure. Mice heterozygous for Smn show up to 50% motor neuron attrition by 6 months of age and are used as a model for mild SMA in humans. To determine both the rate of cellular loss and the molecular events underlying motor neuron degeneration in SMA, motor neuron counts and mRNA q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…It is possible that a specific splicing defect that is detrimental to motor neurons occurs but was not detected in the total RNA sample from spinal cord. The lack of an effect on the level of the majority of the transcripts nevertheless indicates that general Pol II transcription and mRNA turnover have not been significantly affected, consistent with cDNA expression microarray experiments using different SMA mouse models with milder phenotypes (Balabanian et al, 2007;Olaso et al, 2006). In many cases, the aberrant splicing generates an mRNA that contains a premature termination codon.…”
Section: Discussionsupporting
confidence: 69%
“…It is possible that a specific splicing defect that is detrimental to motor neurons occurs but was not detected in the total RNA sample from spinal cord. The lack of an effect on the level of the majority of the transcripts nevertheless indicates that general Pol II transcription and mRNA turnover have not been significantly affected, consistent with cDNA expression microarray experiments using different SMA mouse models with milder phenotypes (Balabanian et al, 2007;Olaso et al, 2006). In many cases, the aberrant splicing generates an mRNA that contains a premature termination codon.…”
Section: Discussionsupporting
confidence: 69%
“…Smn −/− ; SMN2 +/+ ) show clearly discernible loss of neuro-muscular morphology, strong synaptic transmission defects, loss of pre-synaptic inputs to spinal motor neurons, muscle degeneration and eventual death of motor neurons (Balabanian et al, 2007; Jablonka et al, 2000; Monani et al, 2000). Several studies have also used Cre-loxP derived conditional knockout models of SMA in mice to address the question of tissue-specificity of SMN vis-à-vis the incidence of SMA-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The SMN2 gene carries a C-to-T transition leading to aberrant splicing in 80–90% of the SMN2 transcript and loss of exon 7 ( SMN Δ 7 ) resulting in a protein with reduced stability (Lorson et al, 1999; Lorson and Androphy, 2000; Monani et al, 1999). The overall reduction of the SMN protein leads to severe neuromuscular degeneration including the loss of motor neuron cell bodies over time (Balabanian et al, 2007; Jablonka et al, 2000; Monani et al, 2000). SMN is a highly conserved ubiquitously expressed protein that is required critically for normal mRNA splicing since it affects the biogenesis of U snRNP particles across species (small nuclear ribonucleoprotein) (Fischer et al, 1997; Kroiss et al, 2008; Lee et al, 2009; Liu et al, 1997; Meister et al, 2001; Pellizzoni et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, compared with controls, severe SMA mice display an approximate 40% reduction in spinal cord motor neuron number at P5, the late-symptomatic stage (Monani et al, 2000), whereas Smn heterozygotes display a 40% loss at 6 months and a 54% loss at 1 year (Jablonka et al, 2000). In a subsequent study of the heterozygous mice, a reduction of lumbar motor neurons by 28% was reported at 5 weeks and by 30% at 3 months, suggesting once again that there is an early period of susceptibility in which there is greater degeneration of motor neurons, followed by a period of relative stability (Balabanian et al, 2007). …”
Section: Is Smn a General Survival Factor For Motor Neurons?mentioning
confidence: 94%
“…Homozygous Smn deletion results in massive embryonic cell death before implantation (Schrank et al, 1997). Heterozygous null mice lack a marked clinical phenotype, although some reports suggest that there is histologically detectable age-dependent loss of neuromuscular integrity (Schrank et al, 1997; Jablonka et al, 2000; Balabanian et al, 2007). A number of different strategies have been employed to produce models that recapitulate the human genotype (summarized in Table 1, with further information at http://jaxmice.jax.org/list/ra1733.html).…”
Section: Mouse Models Of Smamentioning
confidence: 99%